Neonatal Long-Chain 3-Ketoacyl-CoA Thiolase deficiency: Clinical-biochemical phenotype, sodium-D,L-3-hydroxybutyrate treatment experience and cardiac evaluation using speckle echocardiography - Annemarijne R.J. Veenvliet; Mark R. Garrelfs; Floris E.A. Udink ten Cate; Sacha Ferdinandusse; Simone Denis; Sabine A. Fuchs; Marit Schwantje; Rosa Geurtzen; Annemiek M.J. van Wegberg; Marleen C.D.G. Huigen; Leo A.J. Kluijtmans; Ronald J.A. Wanders; et al. (Molecular Genetics and Metabolism Reports, 2022)
Isolated long-chain 3-keto-acyl CoA thiolase (LCKAT) deficiency is a rare long-chain fatty acid oxidation disorder caused by mutations in HADHB. LCKAT is part of a multi-enzyme complex called the mitochondrial trifunctional protein (MTP) which catalyzes the last three steps in the long-chain fatty acid oxidation. Until now, only three cases of isolated LCKAT deficiency have been described. All patients developed a severe cardiomyopathy and died before the age of 7 weeks. Here, we describe a newborn with isolated LCKAT deficiency, presenting with neonatal-onset cardiomyopathy, rhabdomyolysis, hypoglycemia and lactic acidosis. Bi-allelic 185G > A (p.Arg62His) and c1292T > C (p.Phe431Ser) mutations were found in HADHB. Enzymatic analysis in both lymphocytes and cultured fibroblasts revealed LCKAT deficiency with a normal long-chain 3-hydroxyacyl-CoA dehydrogenase (LCHAD, also part of MTP) enzyme activity. Clinically, the patient showed recurrent cardiomyopathy, which was monitored by speckle tracking echocardiography. Subsequent treatment with special low-fat formula, low in long chain triglycerides (LCT) and supplemented with medium chain triglycerides (MCT) and ketone body therapy in (sodium-D,L-3-hydroxybutyrate) was well tolerated and resulted in improved carnitine profiles and cardiac function. Resveratrol, a natural polyphenol that has been shown to increase fatty acid oxidation, was also considered as a potential treatment option but showed no in vitro benefits in the patient's fibroblasts. Even though our patient deceased at the age of 13 months, early diagnosis and prompt initiation of dietary management with addition of sodium-D,L-3-hydroxybutyrate may have contributed to improved cardiac function and a much longer survival when compared to the previously reported cases of isolated LCKAT-deficiency.